Extrusion-based 3D printing technology in soy protein-based meat analogs: a review - Khalid, Nurul Izzah; Maxy, Dianna; Yong, Amanda Seng Ping; Sulaiman, Rabiha; Noh, Teh Ubaidah; Mohd Ramli, Sharifah Hafiza; Teh, Huey Fang; Kamalbatcha, Zainebbeevi (Wiley-Blackwell Publishing, Inc., 2024)
Extrusion-based 3D printing technology has emerged as a promising method for developing soy protein-based meat analogs, addressing the urgent demand for sustainable and nutritious alternatives to traditional meat sources. There is a growing global interest in soy protein-based diets, driven by environmental sustainability, health, and animal welfare concerns. Extrusion-based 3D printing involves pushing soy protein pastes through a nozzle to develop layers that build up into three-dimensional objects and enable the production of structures closely mimicking the texture and appearance of real meat. Soy proteins, characterized by their high protein content and balanced amino acid profile, are ideal for producing meat-like textures and flavors. This review explores the application of extrusion and 3D printing technologies in soy protein-based meat analog production, emphasizing their potential to replicate the sensory qualities of animal meat. It discusses the advantages and challenges associated with these technologies, including the optimization of printing parameters for consistency and quality. Rheological studies are conducted to achieve smooth extrusion and proper layer formation whereas integrating fats, fibers, and natural flavors to enhance texture and taste. The review provides an overview of extrusion processes, highlighting rheological studies optimizing the flow behavior of soy protein pastes for effective 3D printing. Additionally, it examines textural studies aimed at mimicking the mouthfeel and bite of real meat, as well as printing performance evaluated through shape retention, layer resolution, structural strength, and printing accuracy. Consumer acceptance of soy protein-based meat analogs is also discussed, highlighting the familiarity with soy products and the increasing demand for plant-based alternatives. The review concludes by considering prospects for these technologies, focusing on innovations in extrusion and 3D printing, market trends, and evolving consumer preferences.